Relatório final de estágio curricular em prática veterinária : tratamento de ferida de difícil resolução com Técnica dos 3 L’s e protocolo D.E.L.T.A de reabilitação dinâmica - Cunha, Maria Paula Pereira de Lourenzo [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Relatório do Estágio Curricular em Prática Veterinária apresentado à Faculdade de Ciências Agrárias e Veterinárias, Campus de Jaboticabal, UNESP, como requisito para conclusão do Curso de Graduação em Medicina Veterinária. Descrição dos locais onde foram realizados os estágios, sendo eles: Centro Kawell, Consultório Veterinário Clínica do Rancho e HorseCare. Descrição de caso clínico de ferida de difícil resolução tratada com Técnica dos 3 L's e protocolo D.E.L.T.A. de reabilitação dinâmica com revisão bibliográfica sobre o tema.

Report of the Curricular Internship in Veterinary Practice presented to the College of Agricultural and Veterinary Sciences, Jaboticabal Campus, UNESP, as a requirement for completion of the Graduation Course in Veterinary Medicine. Description of the places where the internships were carried out: Kawell Center, Veterinary Clinic Clínica do Rancho and HorseCare. Description of clinical case of a difficult wound resolution treated with 3 L's technique and D.E.L.T.A. protocol of dynamic rehabilitation with literature review on the subject.
Final report of curricular internship in veterinary practice: treatment of difficult-to-resolve wound with 3 L's Technique and D.E.L.T.A. protocol of dynamic rehabilitation
Keywords: Medicina Veterinária; Feridas; Fisioterapia; Equino